WATER SPRINGS AS A RESOURCE FOR NATURE TOURISM IN LATVIA: A TOURIST PERSPECTIVE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Water springs are considered as one of the important natural resource for tourism due to its socio-economic, cultural, health and religious benefits. Tourists are motivated to visit the water springs due to various reasons like sacredness, health benefits, education and cultural enrichment.  Latvia is blessed with several water springs, which are potential attractions for the sacred water or holy water tourism. There are several studies conducted on various aspects of water springs in general. However, the research in the context of tourism, particularly motivations and interest of tourist is very scant. In this regard, aim of the paper is to know the motivations and potential benefits of the water spring tourism to tourist in Latvia. Initially authors reviewed existing literature to know the state of the spring tourism. Semi structured interviews and online-survey method to obtain visitors responses.  Interviews were held with the visitor, covering various aspects like motivations and benefits of water spring tourism. To the best of the author’s knowledge, very few studies conducted on spring tourism in Latvia, to provide a detailed overview on tourist motivations and potential benefits of visiting water spring tourism. Overall, the study results provide the basis for understanding the most frequently visited water spring resources by the tourists in Latvia. Nature appreciation, natural setting followed by mineral and health benefits are the major reasons to visit the water springs. Further, it allows decision makers to incorporate tourist opinion and their suggestions in the sustainable planning, promotion and management of water springs as tourist destinations in Latvia.